Real-time adaptive optics with pyramid wavefront sensors: part I. A theoretical analysis of the pyramid sensor model. (21st March 2019) - Hutterer, Victoria; Ramlau, Ronny; Shatokhina, Iuliia
Abstract: We consider the mathematical background of the wavefront sensor type that is widely used in adaptive optics systems for astronomy, microscopy, and ophthalmology. The theoretical analysis of the pyramid sensor forward operators presented in this paper is aimed at a subsequent development of fast and stable algorithms for wavefront reconstruction from data of this sensor type. In our analysis we allow the sensor to be utilized in both the modulated and non-modulated fashion. We derive detailed mathematical models for the pyramid sensor and the physically simpler roof wavefront sensor as well as their various approximations. Additionally, we calculate adjoint operators which build preliminaries for the application of several iterative mathematical approaches for solving inverse problems such as gradient based algorithms, Landweber iteration or Kaczmarz methods.